Ptelea Trifoliata - A Review (Advancements in Homeopathic Research, 2024)
Soon after discovery of Ptelea trifoliata in colonial  America, this attractive aromatic shrub became  popular in Old World botanical gardens. First  medical indications as anthelmintic and vulnerary,  by Schoepf in 1787, were extended in nineteenth century homoeopathic literature to include alleged  usefulness as a febrifuge, tonic, and in treatment of  numerous chronic conditions. Presence of berberine,  or other substances reported by early workers, has  not been confirmed.
Keywords: Ptelea trifoliata; Old World botanical; Pielea trifoliata